Pengembangan Pariwisata Berbasis Masyarakat di Blue Lagoon, Sleman Yogyakarta - hafni khairunnisa (IAIN Salatiga, 2019)
This study aims to find out how tourism development strategies are carried out by the Blue Lagoon community. The research method used is a descriptive qualitative research method. Sources of data in this study were obtained from interviews with sources as well as observations and archives or documents, literature studies. The sampling technique uses purposive sampling. Data analysis in this study uses an interactive analysis model. Based on the results of the study it can be seen that the strategy of developing a tourism village carried out by the community is by forming a tourism village management committee, making tour packages, building supporting facilities, promotion programs and cooperation with various interested parties. Through the tourism development strategy, it is seen how tourism empowerment has fostered community participation, established cooperative relationships and improved the economy of the community around the tourism area.